Assessing extratropical impact on the tropical bias in coupled climate model with regional coupled data assimilation. Issue 7 (14th April 2017) - Lu, F.; Liu, Z.; Zhang, S.; Jacob, R.
Abstract: The tropical bias of double‐Intertropical Convergence Zone (ITCZ) has been a persistent feature in global climate models. It remains unclear how much of it is attributed to local and remote processes, respectively. Here we assess the extratropical influence on the tropical bias in a coupled general circulation model dynamically, systematically, and quantitatively using the Regional Coupled Data Assimilation (RCDA) method. RCDA experiments show that the model's double‐ITCZ bias is improved systematically when sea surface temperature, air temperature, and wind are corrected toward real‐world data from the extratropics into the tropics progressively. Quantitatively, the tropical asymmetry bias in precipitation and surface temperature is reduced by 40% due to extratropical impact from outside of 25°. Coupled dynamics, as well as atmospheric and oceanic processes, play important roles in this extratropical‐to‐tropical teleconnection. Energetic analysis of cross‐equatorial atmospheric energy transport and equatorial net energy input are used to explain the changes in the precipitation bias. Plain Language Summary: The tropical bias, especially the simulation of a double‐Intertropical Convergence Zone (ITCZ), has been a persistent problem for even the most advanced global climate models. This paper shows that the tropical bias in a coupled climate model partly comes from outside the tropics. Our experiments utilize coupled data assimilation to systematically and quantitatively assess the influence of extratropical climate on the tropical bias. The results show that the extratropical impact on tropical bias is achieved through atmospheric teleconnection, ocean dynamics, and coupled ocean‐atmosphere processes. The implications from this manuscript could help diagnose and reduce the tropical bias in climate models, while our method is a showcase for using coupled data assimilation to study climate dynamics in coupled systems. Key Points: Extratropical impact on tropical bias is assessed systematically and quantitatively using regional coupled data assimilation (RCDA) Tropical bias in a coupled climate model partly comes from extratropical sources Extratropical impact on tropical bias is achieved through atmospheric teleconnection, ocean dynamics, and coupled processes